2010
DOI: 10.3745/jips.2010.6.2.163
|View full text |Cite
|
Sign up to set email alerts
|

IMTAR: Incremental Mining of General Temporal Association Rules

Abstract: Nowadays due to the rapid advances in the field of information systems, transactional databases are being updated regularly and/or periodically. The knowledge discovered from these databases has to be maintained, and an incremental updating technique needs to be developed for maintaining the discovered association rules from these databases. The concept of Temporal Association Rules has been introduced to solve the problem of handling time series by including time expressions into association rules. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Dafa-Alla et al [11] introduced algorithm IMTAR for incremental mining of TARs using TFP-tree (Total from Partial tree). Fouad et al [23] suggested an incremental temporal association rules mining algorithm called IndxTAR.…”
Section: Incremental Temporal Association Rule Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…Dafa-Alla et al [11] introduced algorithm IMTAR for incremental mining of TARs using TFP-tree (Total from Partial tree). Fouad et al [23] suggested an incremental temporal association rules mining algorithm called IndxTAR.…”
Section: Incremental Temporal Association Rule Miningmentioning
confidence: 99%
“…In dynamic and time-series databases, the size of the database grows as time progresses. The incremental updating procedure is developed to perform maintenance (insertion, deletion, and update) of the patterns and rules without mining the complete updated database from scratch [9][10][11]. Traditional algorithms consider all previous transactions to discover future patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Murugam and Shanmugam (2010) have suggested a cumulative isolation technique to detect MAC and routing attacks in mobile ad hoc networks. Sharif and Ahmed (2010) have found that the existing routing protocols were more inefficient against a wormhole attack on the WSN. In the previous work (Shyamala and Valli, 2009) a TESLA based secure route discovery is suggested for MAODV.…”
Section: Introductionmentioning
confidence: 99%